Potensi Antagonis Bakteri Pelarut Fosfat Asal Tanah Gambut terhadap Bakteri Xanthomonas sp. Penyebab Kanker Daun Tanaman Jeruk Siam Pontianak - Juniarti, Shella Mida; Khotimah, Siti; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Life Science, 2024)
The productivity of Siam citrus in West Kalimantan from year to year has begun to decline, one of the causes is a disease that attacks the plant. One of the diseases that often attack citrus plants is leaf cancer disease caused by the bacterium Xanthomonas sp. Phosphate solubilizing bacteria are one of the rhizosphere bacteria from peat soils that can act as biological control agents in plants. Therefore, this study aimed to determine phosphate solubilizing bacteria from peat soil as a control for leaf cancer of the Siam Pontianak citrus plant caused by Xanthomonas sp. This research was conducted from June 2022 to September 2022, at the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. This study used a completely randomized design (CRD) with each of the 5 treatment levels repeated 3 times to obtain 15 experimental units. Antagonist test in vitro using the dual culture method. The results showed that all phosphate solubilizing bacteria from peat soil Bacillus sp. (SGB1), Bacillus sp. (SGB 2), and Bacillus sp. (SGB 3) have antagonistic potential against Xanthomonas sp. (BP2).